La narrazione come incontro - Ciotti, Fabio; Morabito, Carmela (Moderna/Comparata, 2022)
Narrative has been the subject of theoretical reflection and empirical investigation since Aristotle's Poetics. However, with the turn of the millennium, we are witnessing a real narrative turn in the humanities and social sciences. This volume aims to provide an overview of recent developments in the theoretical analysis of narrative, offering the reader a series of contributions that are organized along the following three theoretical-disciplinary axes: theories of narrative at the intersection of cognitive, evolutionary, and computational approaches; narrative theory and cognitive neuroscience; and narrative and storytelling as socio-communicative phenomena.